Globalization 4.0’s Effects on Internationalization of Higher Education: Technology, Internationalization at Home and New Hubs - Aydin, Oya Tamtekin (Journal of Interdisciplinary Studies in Education, 2021)
Due to globalization, it has been realized that the distance between countries is irrelevant because of the various opportunities offered by technological and transportation advancements. Globalization has also manifested itself in the field of higher education through internationalization. The concept of globalization has evolved with time; its new form is called Globalization 4.0, as referred to at the World Economic Forum 2019, and impacts on the internationalization of higher education. Although the number of students in international circulation in higher education has not decreased, there is an apparent shift in the students’ preferred destinations and motivational factors. This study attempted to understand the changes pertaining to the internationalization of higher education in parallel to global developments. Evaluating the effects of Globalization 4.0 on the internationalization of higher education will provide an important outlook to countries and higher education institutions that seek to update and develop internationalization policies.